Case Study Analysis: The Utilization of Health Services by Citizens at Area of Tangerang Selatan, Indonesia - Permatasari, Putri; Arbitera, Cahya; Wenny, Dwi Mutia (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Citizens are people who have a high risk of exposure to diseases due to unhealthy environmental conditions. This requires citizens to take advantage of health services in order to get optimal examinations. AIM: The purpose of this study was to determine the description and relationship between the characteristics of citizens, the characteristics of health services and the utilization of health services by citizens in the area of Tangerang Selatan, Indonesia in 2020. METHODS: The quantitative research method with cross-sectional design used random sampling techniques. The number of samples was 150 families in the area of Tangerang Selatan, Indonesia. The riset measured data using a questionnaire and collected data by interviewing the respondents. Data analysis used Chi-square analysis and multiple logistic regression analysis. RESULTS: The results showed that the variables related to the utilization of health services were knowledge variable (p = 0.001), number of families (p = 0.021), perception of pain (p = 0.001), and family support (p = 0.030). And the variables that were not related to the utilization of health services were ownership of health insurance (p = 0.750), transportation (p = 0.297), distance (0.340), health information (p = 0.538), and attitudes of health workers (p = 1000). As well as the dominant variable related to the utilization of health services, that is knowledge (p = 0.000) with odds ratio 12.876. CONCLUSION: It is hope that primary healthcare and health workers can involve more communities around the area in their work programs, such as providing health information.